Noninvasive crayfish cardiac and behavioral activities monitoring system - Pautsina, Aliaksandr (Jihočeská univerzita, 2016)
Crayfish provide a model which is simple, has an easily-accessible cardiovascular system and can be maintained in the laboratory conditions; the model has good utility for water quality assessment and ethophysiological studies. A noninvasive crayfish cardiac and behavioral activities monitoring (NICCBAM) system is discussed in the thesis. The system is inexpensive, has relatively few components and permits long-term continuous simultaneous monitoring of cardiac and behavioral activities of several crayfish. Moreover, compared to other available systems, it provides a novel approach of cardiac activity shape analysis which allows improving monitoring accuracy as well as obtaining additional information on crayfish functional state. The NICCBAM system was evaluated by comparing with the well-known electrocardiography system which demonstrated that cardiac contractions with both approaches were synchronous and that both signal shapes were similar. Experiments on crayfish cardiac activity relative to selected odors and chemicals demonstrated the promising potential of cardiac signal shape analysis, not only for detecting changes in the aquatic environment, but also for their classification.
Noninvasive crayfish cardiac and behavioral activities monitoring system
Keywords: NICCBAM; biomonitoring; water quality; Pacifastacus leniusculus; behavior monitoring; NICCBAM; biomonitoring; water quality; Pacifastacus leniusculus; behavior monitoring